1995
DOI: 10.1007/bf00229853
|View full text |Cite
|
Sign up to set email alerts
|

Binaural noise stimulation of auditory callosal fibers of the cat: responses to interaural time delays

Abstract: The corpus callosum, the principal neocortical commissure, allows for the interhemispheric transfer of lateralized information between the hemispheres. The aim of the present experiment was to study callosal transfer of auditory information in the cat, with particular reference to its contribution to sound localization. The corpus callosum was approached under direct visual control, and axonic responses were recorded under light anesthesia using glass micro-pipettes. Results showed that auditory information is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…A previous study in 5- to 10-year-old children using a visuo-motor adaptation paradigm with auditory pre- and post-adaptation test phases showed cross-modal effects in the children, independent of age group (King et al 2009). It is important to note here that azimuthal (in the horizontal plane) sound localization depends to a large part on interaural time differences registered in corpus callosum (CC) fibers, as shown in animal experiments (Poirier et al 1995). In humans, the important role of the CC is illustrated by findings that pointing toward auditory stimuli is less accurate in patients with callosal agenesis (Poirier et al 1993).…”
Section: Introductionmentioning
confidence: 91%
“…A previous study in 5- to 10-year-old children using a visuo-motor adaptation paradigm with auditory pre- and post-adaptation test phases showed cross-modal effects in the children, independent of age group (King et al 2009). It is important to note here that azimuthal (in the horizontal plane) sound localization depends to a large part on interaural time differences registered in corpus callosum (CC) fibers, as shown in animal experiments (Poirier et al 1995). In humans, the important role of the CC is illustrated by findings that pointing toward auditory stimuli is less accurate in patients with callosal agenesis (Poirier et al 1993).…”
Section: Introductionmentioning
confidence: 91%
“…Cells possibly involved in soundã Guarantors of Brain 2002Brain (2002, 125, 1039±1053 source localization were also described by Middlebrooks and Pettigrew (1981). Poirier et al (1989Poirier et al ( , 1995 examined this problem more directly by recording in the auditory portion of the callosum of normal cats. The results showed that callosal ®bres are involved in the processing of both the null interaural time delay, which simulates auditory midline localization, and speci®c, non-zero interaural time delays, suggesting that these ®bres prefer sounds situated at spatial locations other than the midline.…”
Section: Introductionmentioning
confidence: 94%
“…The corpus callosum is the principal neocortical commissure and allows the transfer of sensory and motor information between the hemispheres. In the auditory system, the corpus callosum interconnects different cortical areas, in particular the primary auditory area, which receives input from both ears, thereby providing for the integration of binaural cues (Imig and Brugge, 1978;Kelly and Wong, 1981;Imig et al, 1982Imig et al, , 1986Code and Winer, 1985;Jouandet et al, 1986;Rouiller et al, 1991;Poirier et al, 1995). In fact, sound localization depends upon the combined operation of binaural and monaural cues.…”
Section: Introductionmentioning
confidence: 99%
“…Also, callosal connections are more extensive in the rostral part of A1 (i.e., in the high-frequency representation) (Imig and Brugge, 1978;Bozhko and Slepchenko, 1988). Because of the acoustic shadow of the head, a coherent representation of space throughout the midline requires callosal interactions Imig et al, 1986;Poirier et al, 1995). This is of less significance in the lower frequency range, in which no head shadow exists (Ͻ3-6 kHz for the cat).…”
Section: Hearing Controlsmentioning
confidence: 99%